Development of a Rickettsia bellii-Specific TaqMan Assay Targeting the Citrate Synthase Gene. Issue 6 (29th July 2016) - Hecht, Joy A.; Allerdice, Michelle E. J.; Krawczak, Felipe S.; Labruna, Marcelo B.; Paddock, Christopher D.; Karpathy, Sandor E.
Abstract: Rickettsia bellii is a rickettsial species of unknown pathogenicity that infects argasid and ixodid ticks throughout the Americas. Many molecular assays used to detect spotted fever group (SFG) Rickettsia species do not detect R. bellii, so that infection with this bacterium may be concealed in tick populations when assays are used that screen specifically for SFG rickettsiae. We describe the development and validation of a R. bellii -specific, quantitative, real-time PCR TaqMan assay that targets a segment of the citrate synthase ( glt A) gene. The specificity of this assay was validated against a panel of DNA samples that included 26 species of Rickettsia, Orientia, Ehrlichia, Anaplasma, and Bartonella, five samples of tick and human DNA, and DNA from 20 isolates of R. bellii, including 11 from North America and nine from South America. A R. bellii control plasmid was constructed, and serial dilutions of the plasmid were used to determine the limit of detection of the assay to be one copy per 4 µl of template DNA. This assay can be used to better determine the role of R. bellii in the epidemiology of tick-borne rickettsioses in the Western Hemisphere.